Analisis Peran Likuiditas, NPL, Diversifikasi Dan Size Terhadap Profitabilitas Perusahaan Perbankan Yang Terdaftar Di BEI - Irwan Moridu; Windy Johan; Pandu Adi Cakranegara; Nur Widyawati; Rihfenti Ernayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aim of this study is to determine the effect of diversification, liquidity, size, and NPL on profitability in IDX listedbanking companies from 2018 to 2020. Secondary data is used and collected from the IDX websites. This researchimplemented purposive sampling (as technique sampling) and obtains 20 banks that fulfill the requirements from 46listed banks in IDX. The data were analyzed by using panel regression with Eviews 9. The results of this research aresize and NPL have effect on profitability while diversification and liquidity have no effect on profitability of bankingcompany. Keywords: diversification, liquidity, size, NPL, profitability